Review of Philippine Migration Laws and Regulations: Gains, Gaps, Prospects - Julyn S. Ambito; Melissa Suzette L. Banzon (Philippine Institute for Development Studies (PIDS), 2011)
The Philippines has often been cited as the global model in managing international labor migration. Despite the complexity of our management infrastructure, however, some gaps still remain. This paper reviews the Philippine legal and administrative framework governing the recruitment, documentation, and deployment of Filipino workers abroad. The study finds that although the provisions of the landmark legislation RA 8042, as amended by RA 9422 and 10022, are laudable, some of the key provisions are not absolute. Furthermore, the study finds the need to further strengthen policy implementation as well as the implementing capacity of government agencies.
Keywords: 330; government policies and regulation; Philippines; international labor migration; Philippiner; Internationale Migration; Auslandsaufenthalt; Migrationspolitik; Philippinen